Secular increase in the prevalence of gestational diabetes and its associated adverse pregnancy outcomes from 2014 to 2021 in Hebei province, China - Tian, Mei-Ling; Du, Li-Yan; Ma, Guo-Juan; Zhang, Ting; Ma, Xu-Yuan; Zhang, Ying-Kui; Tang, Zeng-Jun (Frontiers in Endocrinology, 2022)
Objective We aimed to investigate the secular prevalence of gestational diabetes mellitus (GDM) and evaluate its adverse pregnancy outcomes among pregnant women in Hebei province, China. Methods We analyzed the data from the monitoring information management system for pregnant women in 22 hospitals of Hebei province, China. In this study, 366,212 individuals with singleton live births from 2014 to 2021 were included, of whom 25,995 were diagnosed with gestational diabetes. We described the incidence of common complications and further analyzed the clinical characteristics in GDM patients and the relationship between GDM and adverse pregnancy outcomes. Results The top 3 pregnancy complications in Hebei province are anemia, gestational hypertension, and GDM. The average incidence of GDM was 7.10% (25,995/366,212). The incidence rate of GDM significantly increased from 2014 to 2021 (χ2trend = 7,140.663, P < 0.001). The top 3 regions with GDM incidence were Baoding (16.60%), Shijiazhuang (8.00%), and Tangshan (3.80%). The incidence of GDM in urban pregnant women (10.6%) is higher than that in rural areas (3.7%).The difference between the GDM and Non-GDM groups was statistically significant in terms of maternal age, gravidity, parity, education level, and incidence of pregnancy complications (gestational hypertension, heart diseases, and anemia) (P < 0.05). GDM individuals were at significantly increased risk of most assessed adverse pregnancy outcomes, including premature delivery, Cesarean delivery, uterine inertia, neonatal intensive care unit (NICU) admission, Apgar (activity-pulse-grimace-appearance-respiration) score at 1 min, and macrosomia (P < 0.05). The multivariate logistic regression analysis showed that GDM was an independent risk factor in terms of premature birth, Cesarean delivery, uterine inertia, placental abruption, NICU admission, and macrosomia. Conclusion The risk of adverse pregnancy outcome in pregnant women with GDM is significantly increased. In order to reduce the occurrence of adverse pregnancy outcomes, effective interventions are needed.